The use of wool as fiber-reinforcement in cement-based mortar. (15th May 2017) - Fantilli, Alessandro P.; Sicardi, Silvio; Dotti, Francesca
Highlights: Wool and hemp fibers are used herein to reinforce cement-based mortars. Tests are performed on these mortars in accordance with UNI EN 196-1-2006. Similarly to hemp, the fracture toughness increases in mortars reinforced with wool. Hence, by using wool the environmental impact of cement mortars reduces. Abstract: Fiber-reinforced cementitious mortars are widely used in the construction industry. Indeed, the fracture toughness in tension increases with the volume and the aspect ratio (i.e., the ratio between length and diameter) of the fibers, which are generally made with polymeric (e.g., polyethylene, polyvinylchloride, etc.) or inorganic (e.g., glass, carbon, etc.) materials, or with steel. Also vegetal fibers, such as bamboo and hemp, have been used in the last decades to reinforce mortars. Besides, with the aim of introducing animal fibers, the use of wool as fiber-reinforcement is investigated for the first time in the present paper. According to UNI EN 196-1-2006, three point bending tests have been performed on small beams made, respectively, with plain mortar, and mortar reinforced with 1% in volume of wool. To compare the performances with mortars containing vegetal fibers, also beams reinforced with hemp have been tested. In some tests, wool and hemp are previously treated with atmospheric plasma in order to modify the nano-metric properties of the fiber surface. As a result, both the flexural strength and the ductility increase when wool, treated or not, is added to cementitious mortars. Similarly to hemp, wool does improve the mechanical and ecological performances of the mortars, and creates a link between textile and construction markets.